VALORIZATION OF SUPERABSORBENT POLYMERS FROM USED DISPOSABLE DIAPERS AS SOIL MOISTURE RETAINER - Sánchez-Orozco, Raymundo; Timoteo-Cruz, Beatriz; Torres-Blancas, Teresa; Ureña-Núñez, Fernando (International Journal of Research -GRANTHAALAYAH, 2017)
This study was conducted to explore the potential of superabsorbent polymers (SAPs) from used disposable diapers as soil moisture retainer. Swelling behavior of the proposed hydrogel in response to external stimuli such as salt solutions, temperature and pH was studied. In addition, laboratory experiments were carried out to evaluate the effects of incorporation hydrogel on germination of bean (Phaseolus vulgaris L.) and pumpkin (C. pepo) seeds. The structure of the used superabsorbent was characterized by Fourier transform infrared spectroscopy (FTIR). The results indicate that the proposed SAP exhibited a maximum swelling capacity of 189 g-g-1 of dry gel. It was observed that the swelling capacity decreased with an increase in the ionic strength of the swelling medium. When this SAP was mixed with sandy soil, the mixture was able to lose water more slowly. The seeds germination and seedling growth was remarkably influenced by the application of 0.5, 1.0 and 2.0 w/w% of SAP compared to the untreated soil. Therefore, it follows that it is possible to take advantage of SAPs property from used disposable diapers to retain the moisture in soil as an alternative to value the use of such waste, showing that it has potential for agricultural applications.